Representation Of Indigenous Papuans In The Bureaucracy Of Southwest Papua Province: A Representative Bureaucracy Analysis - Dewiyanti Rengen; Hasniati Hasniati; Muh. Akmal Ibrahim; Didik Iskandar (CV. Doki Course and Training, 2026)
Affirmative action has increased the presence of Indigenous Papuans (OAP) in the bureaucracy of Southwest Papua Province, yet numerical representation does not automatically guarantee substantive representation in positions that determine policy direction. This study analyzes the quality of OAP representation through three components of representative bureaucracy: passive representation, linking conditions, and active representation. Using an interpretive qualitative approach with an embedded case study design in the Provincial Government of Southwest Papua, the study involved 25 informants, with data from in-depth interviews, documentation study, and limited observation, analyzed through theory-driven thematic analysis, pattern matching, and explanation building. The findings show that OAP representation is high in number and evenly distributed across ranks, but uneven by role weight—concentrated in supporting positions, while policy-determining positions remain limited. The five linking conditions (discretion, domain relevance, competence and legitimacy, leadership support, accountability) remain weak. Active representation is limited in the policy arena but stronger in service delivery, accompanied by the symptom of substantive roles being carried by other actors. The three components form a tiered chain that breaks at the middle, so that representation is strong in presence but shrinks in influence. The weak conversion stems from fragile evidence-based legitimacy and the absence of capacity development, so that strengthening representation requires building institutional conditions rather than merely adding numbers.